Pharmacokinetics, Safety, and Tolerability of Rolapitant Administered Intravenously Following Single Ascending and Multiple Ascending Doses in Healthy Subjects. Issue 2 (15th June 2018) - Wang, Xiaodong; Zhang, Zhi‐Yi; Wang, Jing; Powers, Dan; Arora, Sujata; Lu, Sharon; Kansra, Vikram
Abstract: Rolapitant is a selective and long‐acting neurokinin‐1 receptor antagonist approved in an oral formulation in combination with dexamethasone and a 5‐hydroxytryptamine type 3 receptor antagonist for the prevention of delayed chemotherapy‐induced nausea and vomiting in adults. The pharmacokinetic and safety profiles of intravenous (IV) rolapitant were evaluated in two open‐label, phase 1 trials in healthy subjects. Single ascending dose (SAD) and multiple ascending dose studies were conducted in one trial (PR‐11‐5012‐C), and a supratherapeutic SAD study was conducted in a separate trial (PR‐11‐5022‐C). In the SAD and supratherapeutic studies, rolapitant maximum plasma concentration, area under the plasma drug concentration‐time curve (AUC) from time zero to time of last measured concentration, and AUC from time zero to infinity increased dose‐proportionally following single IV infusions of 18 to 270 mg. In the multiple ascending dose study, following 10 daily IV infusions of rolapitant 18, 36, or 54 mg, the mean day 10:day 1 maximum concentration ratio was 1.97, 1.52, and 2.07, respectively, and the mean day 10:day 1 ratio of AUC from 0 to 24 hours was 4.30, 4.59, and 5.38, respectively, indicating drug accumulation over time. Across all studies, rolapitant was gradually eliminated from plasma, with a half‐life of 135‐231 hours. Rolapitant was safe and well tolerated across all studies, with no serious or severe rolapitant‐related treatment‐emergent adverse events. The most common rolapitant‐related treatment‐emergent adverse events were headache, dry mouth, and dizziness, which were predominantly mild in severity. Overall, the pharmacokinetic and safety profiles of IV rolapitant were consistent with those of the oral formulation.